Race And Reconciliation : Essays From The New South Africa - Herwitz, Daniel (Book collections on Project MUSE., 2003)
Seeking the timeless through the timely, Daniel Herwitz brings the vast resources of the philosophical essay to bear on the new realities of post-apartheid South Africafrom racial identity to truth commissions, from architecture to film and television. A public intellectuals reflections on public life, Herwitzs essays question how the new South Africa has constructed its concepts of reconciliation and return.